Plan de implementación de un sistema de gestión de seguridad de la información de una entidad del sector público basado en la NTC ISO 27001:2013 (2017)
The connotation of security has been extended over time thanks to the immersion of new information technology systems. Likewise, the instruments to guarantee the protection, confidentiality and treatment of information have become fundamental strategies for guaranteeing the security of public and private organizations. One of these instruments is the ISO 27001 standard, which has become an important guide that involves the different actors of an entity around the protection of information.